Transcriptional Differences Guided Discovery and Genetic Identification of Coprogen and Dimerumic Acid Siderophores in Metarhizium robertsii - Zhang, Jinyu; Zhang, Peng; Zeng, Guohong; Wu, Guangwei; Qi, Landa; Chen, Guocan; Fang, Weiguo; Yin, Wen-Bing (Frontiers in Microbiology, 2021)
Siderophores are small molecular iron chelators and participate in the multiple cellular processes in fungi. In this study, biosynthesis gene clusters of coprogens and dimerumic acids were identified by transcriptional level differences of genes related to iron deficiency conditions in Metarhizium robertsii. This leads to the characterization of new coprogen metachelin C (1) and five known siderophores metachelin A (2), metachelin A-CE (3), metachelin B (4), dimerumic acid 11-mannoside (5), and dimerumic acid (6). The structure of metachelin C (1) was elucidated by NMR spectroscopy and HR-ESI-MS analysis. Genetic deletions of mrsidA, and mrsidD abolished the production of compounds 1–6 that implied their involvement in the biosynthesis of coprogen and dimerumic acid. Interestingly, NRPS gene mrsidD is responsible for biosynthesis of both coprogen and dimerumic acid, thus we proposed plausible biosynthetic pathways for the synthesis of coprogen and dimerumic acid siderophores. Therefore, our study provides the genetic basis for understanding the biosynthetic pathway of coprogen and dimerumic acid in Metarhizium robertsii.